Shock Therapy and Entrepreneurial Flare #Brexit. Issue 2 (21st February 2019) - Culkin, Nigel; Simmons, Richard
Abstract : Purpose: Much has been written about trade deal opportunities after Brexit (e.g. Minford et al., 2017; Singham and Tylecote, 2018) but much less about envisaged "supply side mechanisms" that would translate a Brexit shock into improved UK competitive performance. Indications as to the supply side mechanisms involved can be found in some pro-Brexit writings and speeches and revolve around cutting regulation and reducing taxation, to spur innovation entrepreneurship. The authors contend that these measures align to a broad set of policy measures associated with Economic Shock Therapy, the Laffer Curve and the associated "Washington Consensus" (Williamson, 2005 ). The authors are looking to stimulate a conversation around whether these measures are most likely to stimulate entrepreneurial innovation and growth. The authors open by contrasting these concepts to growth equilibrium dynamics drawn from Wicksell, Keynes and Schumpeter – and by implication dynamic Walrasian General Equilibrium – to pose the question, is entrepreneur-led growth best led via slashing regulations and taxes or by focussing on correcting existing market failures? The purpose of this paper is to promote controversy and debate as to which "supply side measures" are most effective in enabling entrepreneurial growth. Design/methodology/approach: The authors briefly review the pro-Brexiteer economic framework and relate this to broader Economic Shock Therapy and Laffer Curve concepts; how these have been applied and how some argue they can become "supply side" enablers in a positive Brexit innovation and entrepreneurship transformation. By drawing upon fundamental economic relationships such as Wicksell's (1898) "Natural Rate of Interest", the authors highlight the importance of information asymmetry and regulatory distortion in financial markets, resulting in some entrepreneurs (and associated innovations) failing to receive the capital their project merit. The authors pose the question, whether Shock Therapy, Laffer Curve type tax cuts and any Brexit "bonfire of regulation" will raise entrepreneurial growth and success. Findings: Both Shock Therapy and Laffer Curve inspired tax cuts have a patchy record of success, despite notable achievements in post-1991 Poland. The authors stress entrepreneurs drive innovation and growth, and a key support to them requires correcting "access to finance" market failures. It is questionable if Economic Shocks contribute anything to resolving this fundamental problem. Originality/value: The authors open the supply side debate on anticipated "Brexit Transformation" in the context of long standing (some maybe long forgotten) theoretical understandings, thereby posing the question as to whether potential Brexit-related deregulation, tax cuts and "Economic Shock" therapy are likely to raise entrepreneurial competitive advantage and success rates. Market failure in financial market support for small firm growth and innovation needs are highlighted. Arguably, economic growth and innovation would be better sustained by addressing these failures, than introducing the "unknowns" and risks associated with a substantial Economic Shock.